The Interaction of Insulin and Pituitary Hormone Syndromes - Schernthaner-Reiter, Marie Helene; Wolf, Peter; Vila, Greisa; Luger, Anton (Frontiers in Endocrinology, 2021)
Pituitary hormone axes modulate glucose metabolism and exert direct or indirect effects on insulin secretion and function. Cortisol and growth hormone are potent insulin-antagonistic hormones. Therefore impaired glucose tolerance, elevated fasting glucose concentrations and diabetes mellitus are frequent in Cushing’s disease and acromegaly. Also prolactinomas, growth hormone (GH) deficiency, hypogonadism and hypothyroidism might be associated with impaired glucose homeostasis but usually to a lesser extent. Therefore glucose metabolism needs to be closely monitored and treated in patients with pituitary adenomas. Correction of the pituitary dysfunction is frequently followed by improvement of glucose homeostasis.